Investigation of sodium fire aerosol diffusiophoresis deposition in concrete gaps during the processes within nuclear power plants - Yichen Li; Tiancai Liu; Huanjun Zhu; Xiangyu Yan (International Journal of Advanced Nuclear Reactor Design and Technology)
Sodium fire accidents are among the high-risk incidents that nuclear power plants with sodium-cooled fast reactors pay close attention to. Sodium fire reactions can generate a considerable amount of heat and aerosols within a short period. To analyze the influence, brought about by the aerosol migration after the sodium fire accident in the process of nuclear power plants, considering the migration process of aerosol particles within the concrete cracks of the walls in it and the concentration changes caused by the steam condensation due to the low-temperature walls. This research establishes a diffusiophoresis model of sub-micron particles under the condition of mixed gas condensation. Simulations were carried out for particles of different sizes under different steam content conditions. The results demonstrate that the diffusiophoresis effect caused by gas condensation within the concrete cracks in the process areas of nuclear power plants has played a positive role in reducing sodium fire aerosol leakage. The penetration coefficient of aerosols within the concrete cracks can be reduced by 6 %. On the one hand, it is discovered that the particle size and steam content have a significant impact on the diffusiophoresis. On average, for every 5 % increase in the steam content in the environment, the penetration coefficient of particles decreases by approximately 2 %. On the other hand, it is found that the aerosol particles generated in the initial stage of the sodium fire reaction and the end of the combustion are more susceptible to the diffusiophoresis effect.